A Study of Antibioactivity of Nanosilver Colloid and Silver Ion Solution - Kuo-Hsiung Tseng; Heng-Lin Lee; Der-Chi Tien; Ya-Lan Tang; Yi-Syuan Kao (Advances in Materials Science and Engineering)
The colloidal silver solution was successfully prepared in dielectric fluid by using electrical spark discharge (ESD) without any surfactants. It does not require the toxic chemical agents in the process, which may affect the effectiveness of nanosilver colloid as an antibacterial agent. Nanocolloidal silver produced by ESD is characterized as low cost, zero environmental pollution, continuous, and rapid mass production process. In order to test the effect of antibioactivity, nanosilver dough was tested; the silver nanofluid was prepared by ESD machine, made into dough at different concentrations, and fermented for three hours in order to observe changes in the diameter of the dough. The results showed that the effect of effectiveness of nanosilver at the concentration of 100 ppm was weak, whereas the effect of 60 ppm silver ion (100 ppm AgNO3) was significant, as the dissociation rate of silver ion concentration correlates to the antibioactivity.